The Inuit and Sovereignty: The Case of the Inuit Circumpolar Conference and Greenland - Gerhardt, Hannes (Politik, 2011)
This paper addresses the positioning of the Inuit with regard to the institution of sovereignty within the broader context of an Arctic region that is becoming increasingly territorialized. First, the paper considers the Inuit Circumpolar Conference (ICC) and its emphasis on the need to think past a strict Westphalian conception of bounded state sovereignty in favor of a circumpolar cooperation that recognizes the Inuit people as key actors within any regime of Arctic governance. Juxtaposed to the ICC, however, the paper goes on to analyze the Greenland self rule government, which, in positioning itself for the creation of a future independent “Inuit state”, takes a much more traditional approach to international relations, thus embracing a more territorial conception of sovereignty. A rift is hence uncovered in the way that Inuit identity and sovereignty are conceived by the ICC and the Greenlandic self rule government. The paper continues to consider the possible impact of an independent Greenland on the future of Inuit self-determination more generally.